Diffusion of Regional Government Credit Card Innovation in Accelerating Financial Transactions in Bekasi Regency, West Java Province (International Forum of Researchers and Lecturers, 2025)
This study analyzes the diffusion of Local Government Credit Card (KKPD) innovation in accelerating financial transactions in Bekasi Regency, West Java Province. The purpose of this study is to analyze the implementation of KKPD innovation diffusion, analyze the barriers to the diffusion of KKPD innovation, and recommend alternative policy solutions in overcoming obstacles to the implementation of expenditure payments. Using a qualitative research approach with observation, interview, and documentation data collection techniques. The results of the study show that the diffusion of KKPD innovation has been carried out in stages starting with 3 (three) SKPDs out of 60 existing SKPDs. The obstacle is that not all SKPDs immediately feel the benefits because the implementation of KKPD is still limited, there is no synchronization between KKPD and the Regional Government Information SIstem (SIPD), the procedure for using KKPD is still complicated and adds to the administrative burden. An alternative policy solution is the issuance of a Regent Regulation clarifying the SOP for each SKPD and accelerating the synchronization of KKPD with SIPD. Increasing human resource capacity through continuous training and mentoring, expanding pilot projects to many SKPDs, carrying out periodic monitoring, evaluation and supervision. Recommendations to the Bekasi Regency Government (BPKD Bekasi Regency) are the need to prepare internal SOPs for each SKPD related to the use of KKPD, Treasurer Training and Financial Human Resources, accelerate the integration of the KKPD sIstem with SIPD so that transactions are automatically recorded in the regional financial management sIstem.